GAMBARAN POLA KOMUNIKASI ORANG TUA DAN PERILAKU ANAK PENGGUNA VIDEO GAME DI SMP N 3 GAMPING SLEMAN - Rifaldi Zulkarnaen; Sri Hendarsih; Eko Suryani (Poltekkes Kemenkes Yogyakarta, 2018)
By the development of the time, video games technology increasingly popular in the society starting from children to adults. The video games effect can disturb the growth and development of the children. Parents must give more concern and attitude for video games users. This concern and attitude must in the way how parent’s communication pattern. The effective communication can controled video games users. Children with the good communication pattern can give good or bad estimation if the childrens addiction from video games. This is too give the children bad attitude like estimation from parents.Purpose. The purpose of the research is to discribe the parents communication patterns and behavior of children user video games in SMP N 3 Gamping, Sleman. Methods. The method used is discriptive research. The study conducted in marc 2015. The research locatioan in SMP N 3 Gamping Sleman Yogyakarta. the subjects were child early teens video games users as many 49 users. The research used questionnaire about parents comunication pattern and behavior of child video game users. Last the analysis used distribution frequency.Results. The research shows 44,9% of parents using authoritaive communication pattern, 18,4 % parents used permissive communication pattern and 36,7 % parents used authotarian communication pattern. While the behavior of the children’s video game users are good is 81,6 % and 18,4 % are bad.Conclusion. Majority, parents used authoritative communication patterns to chlid of video games users and users have good behavior.